Impact of the adoption of Brachiaria grasses: Central America and Mexico - Holmann, Federico J.; Rivas Ríos, Libardo; Argel M., Pedro J.; Pérez, E. (2004)
Livestock production plays a key role in tropical Latin America in a changing economic environment. This study focuses on documenting the transformations of extensive production systems by using superior forage germplasm supplied by regional research systems. The adoption of improved Brachiaria grasses was evaluated from 1990 to 2003 to estimate its impact in terms of animal productivity and income in Central America and Mexico. Information on seed sales in the local market made it possible to estimate the areas planted and the value of additional milk and beef production attributable to adoption. Mexico presents the highest volume of marketed seed and of area established with improved pastures. Among Central America countries, Costa Rica was outstanding in terms of the high volume of seed sold and the area planted, followed by Honduras, Nicaragua, and Panama. The annual growth rate of seed sales was very high during the study period, reaching 32% in Mexico, 62% in Honduras, 45% in Nicaragua, 39% in Costa Rica, and 54% in Panama. The area planted with Brachiaria species during this period totaled 6.5% of the total surface of permanent grasses in Mexico, 12.5% in Honduras, 1.0% in Nicaragua, 18.7% in Costa Rica, and 0.1% in Panama. Excluding Nicaragua and Panama, where adoption is low, Brachiaria grasses account for 24%-55% of total annual milk production and for 5%-18% that of beef. These figures clearly demonstrate that those adopting new Brachiaria cultivars are farmers mainly oriented toward milk production and, to a lesser extent, beef. In monetary terms, the value of additional production attributable to the adoption of Brachiaria grasses in the selected study countries was estimated at US$1084 million per year, 78% corresponding to milk and 22% to beef. Due to the magnitude of the livestock sector in Mexico, adoption generates slightly more than 80% of production profits. Study results indicate that the investment of public funds in Central America and Mexico to support the International Network for Evaluation Tropical Pastures (RIEPT, its acronym in Spanish) paid off in terms of adoption of improved grasses and significant increases in the supply of milk and beef, fundamental items in the diet of consumers from all income levels in the region.